Magnetic properties and critical behavior of random alfa-FeMnAl alloys: An Ising Monte Carlo study (2005)
ABSTRACT: The effect of atomic disorder, dilution, and competing interactions upon the magnetic properties of alfa-FeMnAl alloys with different stoichiometries is addressed by means of the Monte Carlo method. Magnetization per site, specific heat, and magnetic susceptibility were computed as a function of temperature on the basis of a Metropolis dynamics, from which critical exponents were estimated. Simulation was carried out in the frame of a random site-diluted three-dimensional Ising model with nearest-neighbor interactions, where Fe-Fe ferromagnetic and Fe-Mn, Mn-Mn antiferromagnetic interactions, as well as the Al dilutor effect, were taken into account. Results, which are summarized in a magnetic phase diagram, reveal the occurrence of several phases including reentrant and pure spin-glass behaviors below around 11 K, and a ferromagnetic to paramagnetic phase transition at temperatures between 100 K and 400 K. Finally, critical exponents, which are consistent with Harris criterion, are also compared to those obtained in other 3D random Ising models.